SUBJECTS OF DISCIPLINARY LIABILITY FOR CORRUPTION OFFENSES UNDER THE LABOUR LAW OF UKRAINE - Вишновецька, Світлана Василівна; Вишновецький, Вадим Михайлович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: to research the peculiarities of structure of subjects of disciplinary liability for corruption offenses determined by the labour legislation of Ukraine. Research methods: documentary analysis and synthesis, comparative analysis, objective truth, cognitive and analytical, etc. Results: the authors generalized structure of subjects of disciplinary liability for corruption offenses determined by the labour legislation of Ukraine. Discussion: legal nature of the corruption phenomenon, problems of corruption manifestations in labour relations and ways to overcome them. Corruption is traditionally researched as a phenomenon that is inherent in the public sphere only, and corruption is often ignored in the private sphere. It is connected with many scientific and legal traditions common to many countries based on the doctrines of non-interference with the private sphere. Some scholars generally deny the existence of corruption in labour relations. At the same time, in the labour relations the senior manager has practically unlimited initiative in the issues of personnel appointments, dismissals and transfers. Thus, the above mentioned testifies to the relevance of research of this phenomenon in the context of labour relations. It is concluded that the subjects of disciplinary responsibility for corruption offenses within the labour relations are officials, i.e. persons holding positions related to the performance of organizing and administrative, or administrative and economic functions in the process of performing their professional obligations under the labour agreement. This includes, in particular, the obligations to manage the work collective, production activity of separate employees at enterprises, institutions or organizations regardless of the forms of ownership. We mean the heads of enterprises, institutions and organizations, their deputies, heads of structural divisions (heads of shops, heads of divisions, laboratories, departments), their deputies, persons who manage sections of works (foremen, construction superintendents, team leaders, etc.), heads of planning and economic, supplying, financial departments and services, heads of warehouses, shops, workshops, ateliers, their deputies. Therefore, job descriptions as an important local regulation of a particular enterprise play an important role in qualifying such obligations.